PENGARUH LAMA WAKTU PEMANASAN TERHADAP KUALITAS ORGANOLEPTIK DAN FISIK BISKUIT BIOSUPLEMEN “MORINGA” KELINCI (BBCi) - Efi Rokana; Mubarak Akbar; Dyah Arie WK (Universitas Tribhuwana Tunggadewi, 2022)
This study aimed to determine the effect of heating time duration on the organoleptic and physical quality of rabbit moringa bio supplement biscuits (BBCi). This study used a completely randomized design (CRD) with 5 treatments and six replications. The research treatments were the duration of time heating at a temperature of 100°C (P), namely P1= 45 minutes; P2= 60 minutes; P3 = 75 minutes; P4 = 90 minutes; P5 = 105 minutes. The research variables included an organoleptic test, density test, water absorption, and shatter test. The results showed that different heating times showed a highly significant effect (P0.01) on the density and shatter test of BBCi, while the variables of color, smell, texture, density, and water absorption showed no significant effect. (P0.05). The highest average density and shatter test (%) of BBCi were 3.50±0.55 (P4) and 86.04±6.65 (P5). Whereas the lowest average density and shatter test (%) of BBCi was shown in the P1 = 1.00±0.00 and 11.20±12.32. The conclusion was that the best BBCi density and shatter test values were found in the treatment with a duration heating time of 90 and 105 minutes.